Allotherme Vergasung von Braunkohle und Gasreinigung mit integrierter Abtrennung von CO2 zur Optimierung des C/H/O-Verhältnisses im Produktgas - Treiber, Peter; Neubert, Michael; Leimert, Jonas; Karl, Jürgen (DGMK-Fachbereichstagung: Konversion von Biomassen und Kohlen, 2016)

Combining the Heatpipe Reformer technology with hydrogen-intensified methanation for production of synthetic natural gas - Leimert, Jonas; Neubert, Michael; Treiber, Peter; Dillig, Marius; Karl, Jürgen (Applied Energy, 2018)

Dry Reforming of Methane Using a Nickel Membrane Reactor - Leimert, Jonas; Karl, Jürgen; Dillig, Marius (Processes, 2017)

Einsatz von Nickelmembranen zur in-situ Wasserstoffabtrennung im Heatpipe Reformer - Leimert, Jonas; Karl, Jürgen (Jahrestreffen der ProcessNet-Fachgruppe Hochtemperaturtechnik, 2016)

Generation of Hydrogen from Solid Feedstock Using the Heatpipe Reformer Technology with in-Situ Hydrogen Separation By Nickel Membranes - Leimert, Jonas; Karl, Jürgen (2016 AIChE Annual Meeting, 2016)

Herstellung von Wasserstoff auf Basis der Heatpipe Reformer Technologie - Leimert, Jonas; Karl, Jürgen (DGMK Tagungsbericht zur Fachbereichstagung "Konversion von Biomassen", 2014)

Herstellung von Wasserstoff auf Basis der Heatpipe Reformer Technologie mit verbessertem Kaltwirkungsgrad - Leimert, Jonas; Karl, Jürgen (1. Forschungskolloquium Bioenergie, 2015)

Herstellung von Wasserstoff durch Nutzung der Heatpipe Reformer Technologie mit integrierter Wasserstoffabtrennung - Leimert, Jonas; Karl, Jürgen (ProcessNet 2017, Jahrestreffen Fachgruppe Energieverfahrenstechnik, 2017)

Hydrogen concentration measurement in high temperature applications using hydrogen permeation - Leimert, Jonas; Bartolf, Alexander; Karl, Jürgen (International Journal of Hydrogen Energy, 2016)
With the increasing use of hydrogen in energy process engineering and as chemical reactant, the importance of hydrogen sensors is rising. However, there are few established methods to measure the hydrogen concentration of a gas-mixture at high temperatures. Also the in situ measurement at these temperatures in chemical reactors is challenging. A sensor, which is based on hydrogen permeation, could be a cheap and practical solution for the in situ measurement at high temperatures.A permeation hydrogen sensor for the measurement of the hydrogen partial pressure was developed and built. The concept of the sensor is a small, hermetically sealed nickel tube working as a hydrogen permeable membrane filled with pure hydrogen. It is in contact with the measurement gas and connected to a pressure sensor. Under stationary conditions a equilibrium between the hydrogen partial pressure of the tube and the measurement gas will be established. Since the tube is filled only with hydrogen, the pressure sensor connected with the nickel-tube measures the hydrogen partial pressure of the measurement gas.Such a sensor was modeled, developed, built and characterized. The most important calculations, the general design of the sensor as well as the most important results of the experiments are presented in this paper. The sensor worked with a good accuracy and showed a response time of about 1000 s at 60 °C and 200 s at 900 °C. A response time lower than 200 s for temperatures above 600 °C is possible with an improved sensor design. Also, an in-situ measurement of the steam content inside a shift reactor was conducted, the results matched the calculated steam contents from a reactor balance very precisely.
Keywords: Hydrogen; In-situ measurement; Membrane; Permeation; Sensor

Hydrogen inactivation of liquid metal heat pipes - Leimert, Jonas; Dillig, Marius; Karl, Jürgen (International Journal of Heat and Mass Transfer, 2016)
Keywords: Gasification; Heat pipe; Heatpipe Reformer; Hydrogen; Hydrogen permeation

Hydrogen production from solid feedstock by using a nickel membrane reformer - Leimert, Jonas; Dillig, Marius; Karl, Jürgen (Journal of Membrane Science, 2018)

Integrated Syngas Cleaning and CO2 Removal for Medium-scale Coal-to-SNG Plants - Treiber, Peter; Leimert, Jonas; Neubert, Michael; Karl, Jürgen (Synthesis Gas Chemistry - DGMK Conference, 2015)

Nickel membranes for in-situ hydrogen separation in high-temperature fluidized bed gasification processes - Leimert, Jonas; Karl, Jürgen (International Journal of Hydrogen Energy, 2016)
The Heatpipe Reformer provides an allothermal gasification process for the generation of hydrogen-rich synthesis gas. This synthesis gas can be used for generation of hydrogen for applications like fuel cells, engines, storage or the chemical industries. Conventional processes for hydrogen production involve CO Shift reactors to enhance hydrogen yield followed by hydrogen separation using gas scrubbing technology. The Institute of Energy Process Engineering (FAU-EVT) follows the approach to apply hydrogen permeable membranes as separation step directly in the reformer. This also allows higher hydrogen yields due to an additional shift of the gasification reactions to the product side as one product is continuously removed. This paper gives an overview on membranes in high temperature applications. It focuses on the temperature range from 750 to 900 °C required for biomass gasification processes. Existing approaches to high temperature hydrogen separation like palladium composite membranes or ceramic materials show advantages and disadvantages mainly regarding stability and prices. The presented approach applies commercial nickel capillary tubes as membranes. Vacuum increases the partial pressure difference between permeate and retentate. This remedies the need for a sweep gas, which is needed with all membranes that cannot withstand a physical pressure difference. In the experimental section several commercial nickel capillaries were tested for their hydrogen permeability and the results from a parameter study regarding the influence of synthesis gas components like CO, CH and HO on permeation are shown. The nickel membranes were also tested in hydrogen containing HS, which can be present in synthesis gas in concentrations of up to 1000 ppm.
Keywords: Gasification; Heatpipe Reformer; Hydrogen; Hydrogen permeation; Membranes; Nickel

Performance and efficiency of the Heatpipe Reformer gasification system - Leimert, Jonas; Karl, Jürgen (Regatec 2017, 2017)

Performance of a 100 kW Heatpipe Reformer operating on Lignite - Leimert, Jonas; Treiber, Peter; Neubert, Michael; Sieber, Aaron; Karl, Jürgen (Energy & Fuels, 2017)

Planar high temperature heat pipes for SOFC/SOEC stack applications - Dillig, Marius; Leimert, Jonas; Karl, Jürgen (Fuel Cells, 2014)
Keywords: Heat Transfer; Solid Oxide Fuel Cell; Stack Design; Thermal Transient Performance

The Heatpipe Reformer with optimized combustor design for enhanced cold gas efficiency - Leimert, Jonas; Treiber, Peter; Karl, Jürgen (Fuel Processing Technology, 2016)
Keywords: Cold gas efficiency; Combustion; Emissions; Gasification; Heatpipe Reformer